Systemic Medication Use and the Incidence and Growth of Geographic Atrophy in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT) - Delu, Song; Peiying, Hua; Brian L, VanderBeek; Joshua L, Dunaief; Juan E, Grunwald; Ebenezer, Daniel; Maureen G, Maguire; Daniel F, Martin; Gui-Shuang, Ying (Retina (Philadelphia, Pa.), 2021)
To determine associations of systemic medications with the incidence and growth of geographic atrophy (GA) in participants of the Comparison of Age-related Macular Degeneration (AMD) Treatments Trials (CATT). Participants of CATT with new untreated choroidal neovascularization in the study eye (one study eye per participant) were randomized to receive treatment with bevacizumab or ranibizumab. Participants were released from clinical trial treatment at 2 years and examined at approximately 5 years. Color fundus photographs and fluorescein angiograms taken at baseline, years 1, 2 and 5 were assessed for presence and size of GA by two masked graders. Participants were interviewed about systemic medication use at baseline. Systemic medications previously reported to be associated with AMD were evaluated for associations with GA incidence in study eye using univariable and multivariable Cox models, and for association with the GA growth using linear mixed effects models. In multivariable analysis of 1011 study eyes without baseline GA, systemic medications including cholinesterase inhibitor, ACE inhibitors, calcium channel blockers, beta-blockers, diuretics, aspirin, steroids, statins, hormone replacement therapy, antacids, and drugs targeting G protein-coupled receptors, were not associated with GA incidence in the study eye (all adjusted hazard ratios ≤1.86, p≥0.18). In multivariable analysis of 214 study eyes with longitudinal GA size measurements, calcium channel blockers were associated with higher GA growth rate (0.40 vs 0.30 mm/year, p=0.02). None of systemic medications analyzed were associated with GA incidence. However, calcium channel blockers were associated with higher growth rate of GA in the study eye.